All kinds of children - Simon, Norma; Paterson, Diane, 1946- (Morton Grove, IL : Whitman, 1999)
Presents the things that all children over the world have in common, including their need for food, clothes, people to love them, and the opportunity to play.
Book Links (A.L.A.)
School Library Journal
Book Links (A.L.A.), January 2004
School Library Journal, June 1999
2.8
K-3.
Keywords: Children -- Juvenile literature; Children -- Pictorial works -- Juvenile literature; Children; Children